Mitologi Lakon Wahyu Eka Bawana dalam Pandangan Masyarakat Sangiran - Kuncoro, Bimo; Sarwanto, Sarwanto (Pascasarjana ISBI Bandung, 2016)
Lakon Wahyu, which is a kind of Lakon Carangan, has been increasingly requested in the last two decades by penanggap wayang (those who summon wayang) in Sangiran region. The high request is predicted because of those who summon this Lakon hope for blessing. There is a belief for generations among Sangiran people that summoning Lakon Wahyu will make their life peaceful and prosperous. LakonWahyu Eka Bawana which tells about the trip of Puntadewa in ge!ing the divine revelation through meditation becomes the main choice of the Sangiran society. They believe that after summoning the Lakon, they will get good impact in their life. Keywords: mythology, lakon Carangan, belief, value, Wahyu Eka Bawana